Analysis of enterprise profitability with application of method of diversifying Analiza rentowności przedsiębiorstwa z wykorzystaniem metody różnicowania - Anna Bieniasz (Journal of Agribusiness and Rural Development, 2008)
The causal analysis of enterprise profitability was presented in the article. The analysis was widened for determining power and direction of the influence of chosen factors on the profitability of own capital. The conducted analysis of own capital profitability in chosen enterprise showed, that in 1997-2006 the level of ROE was often influenced by the change of return on assets than capital multiplier. The changes of assets profitability to larger degree were caused by changes of sale profitability than total assets turnover. Both the model Du Pont, as well as the method of diversifying are not only useful for explain-ing reasons for developing the profitability of assets, or of the return on equity, but above all can be used while undertaking the decision concerning futures.